2017
DOI: 10.1007/s00421-017-3576-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of post-absorptive and postprandial moderate exercise on markers of inflammation in hyperglycemic individuals

Abstract: Moderate exercise increases sVCAM-1 in hyperglycemic individuals, whereas it does not affect CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In women, serum sVCAM-1 is inversely correlated with visceral adipose tissue [41]. In persons with hyperglycemia, moderate exercise was shown to increase sVCAM-1 [42]. …”
Section: Discussionmentioning
confidence: 99%
“…In women, serum sVCAM-1 is inversely correlated with visceral adipose tissue [41]. In persons with hyperglycemia, moderate exercise was shown to increase sVCAM-1 [42]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, a growing body of evidence suggests that the interaction between exercise timing and the timing of food intake may play an important role in the modulation of the circadian clock and the prevention of metabolic diseases, such as T2DM 65 . In line with this, a single bout of postprandial treadmill walking, compared with treadmill walking in a fasted state, further reduced glycemic excursions and glycemic variability, measured by CGM, over the next 22 h in 12 patients with T2DM 66 . A randomized crossover trial including 77 healthy individuals revealed that different exercise bouts performed early after meal, but not in the fasted state, led to significant reductions in postprandial glycemia 67 .…”
Section: The Role Of Exercise Timing In Metabolic Health: Clinical Im...mentioning
confidence: 74%
“…65 In line with this, a single bout of postprandial treadmill walking, compared with treadmill walking in a fasted state, further reduced glycemic excursions and glycemic variability, measured by CGM, over the next 22 h in 12 patients with T2DM. 66 A randomized crossover trial including 77 healthy individuals revealed that different exercise bouts performed early after meal, but not in the fasted state, led to significant reductions in postprandial glycemia. 67 Also, a trial conducted in 54 healthy postmenopausal women demonstrated that 2-h moderate-intensity acute exercise performed 1 h after meals was more effective in reducing insulin resistance than exercise performed 1 h before meals.…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…There was also no beneficial effect of either exercise condition on postprandial glucose responses in comparison with the no-exercise condition. This is perhaps unsurprising, given that studies have demonstrated that 60 min of treadmill walking in the fasted state has no effect on glucose responses to a mixed-macronutrient meal in persons with obesity (37) and hyperglycemia (40). An increased rate of appearance of glucose from the liquid meal during the initial 3-h postexercise period is likely to be the reason for the lack of difference in postprandial glucose, offsetting the increased clearance rate (41).…”
Section: Discussionmentioning
confidence: 99%